Perencanaan Strategis Sistem Informasi di PT VE - Janari, Elisabeth Keisara Garning; Abdillah, Lufty (UNIVERSITAS KALBIS, 2024)
PT VE is a general contractor company that supplies any tools in form of equipment rental for mining corporations in Indonesia. Nowadays, PT VE has an integrated IS for just a few and not for all Departement in the company. Based on this phenomenon some Departement may generates redundant data, and generates ineffectively work process because doing the same recurrent job. The purpose of this study is to make IS/TI Strategis Planning in PT VE by identifying business and IS/IT strategies then conforming them. A methodology this study use is Ward & Peppard verses and uses SWOT, PEST, McFarlan Strategic Grid, Porter’s Five Forces Analysis,Value Chain Analysis, CSF for analysis tools. The result of this study is an application portfolio that might become future reference for establish or developing systems to support the business objectives.